Escape to the Maldives [videorecording (DVD)] - Spacek, Libor; Dolezalova, Petra (Galloping Films, 2022)
The Maldives are a paradise in the Indian Ocean. Swaying palms, white sandy beaches, and deep blue shallow lagoons with live coral reefs expose flowering gardens, where each organism is perfectly connected to the functioning of the surrounding microworld.